Hybrid Hydrogel Composed of Hyaluronic Acid, Gelatin, and Extracellular Cartilage Matrix for Perforated TM Repair - Wang, Yili; Wen, Feng; Yao, Xueting; Zeng, Lulu; Wu, Jiaming; He, Qinhong; Li, Huaqiong; Fang, Lian (Frontiers in Bioengineering and Biotechnology, 2021)
A novel series of composite hydrogels, built from the three components (i), hyaluronic acid methacryloyl (HAMA); (ii), gelatin methacryloyl (GelMA) and (iii), extracellular cartilage matrix (ECM) was prepared and studied regarding the possible utility in the surgical repair of damaged (perforated) tympanic membrane. Noteworthy is component (iii), which was harvested from the ribs of α-1,3-galactosidyltransferase-knockout (α-1,3 GalT-KO) pigs. The absence of α-1,3-galactosyl glycoprotein is hypothesized to prevent rejection due to foreign-body immunogenicity. The composite hydrogels were characterized by various in various aspects, using a variety of physicochemical techniques: aqueous swelling, structural degradation, behavior under compression, compressive and morphology, e.g.. In vitro biocompatibility was assessed by the CCK-8 and Live-Dead assays, and through cytoskeleton staining/microscopy. Alcian blue staining and real-time PCR (RT-PCR) were performed to examine the chondrogenic induction potential of the hydrogels. Moreover, a rat tympanic membrane defect model was used to evaluate in vivo performance of the hydrogel in this particular application. Taken together, the results from this study are surprising and promising. Much further development work will be required to make the material ready for surgical use.